A COVID-19 outbreak linked to a funeral event: an investigation in Phra Kaeo, Sangkha, Surin, October 2021 - Boonrumpai, Krittinan; Sornsurin, Warodom; Sukkasem, Inchat; Monpangtiem, Kannika; Sanmai, Sattawat; Prasatthong, On-u-sa; Sermjan, Sukanda; Intayung, Ajchara; Thammawijaya, Panithee; Jiraphongsa, Chuleeporn (Disease Control Journal, 2023)
Despite the downtrend of Coronavirus Disease 2019 (COVID-19) cases in Thailand in late 2021, many provinces face clusters of COVID-19 associated with rites, rituals, ceremonies, and funerals. On October 5, 2021, the Joint Investigation Team was notified by Surin Provincial Health Office about a COVID-19 village cluster in Sangkha, Surin. We investigated this cluster to describe the characteristics of the cases, identify sources and risk factors of the infection, determine the vaccine's effectiveness and preventive measures against the disease, and support the local team's work. We conducted a descriptive study by reviewing case registrations, medical records, and vaccination databases. We surveyed the village and interviewed health personnel and villagers. We identified potential risk factors of infection and calculated vaccine and preventive measure effectiveness using a case-control study. We found 146 confirmed cases in several villages. A high attack rate (AR) was found in Moo 1 and 11 (AR 11.0% and 10.9%, respectively). The 1-dose vaccine coverage in Moo 1 and 11 was 11.3%. Seventy-two percent of cases were symptomatic, and 37.7% of patients developed pneumonia during admission. No death was reported. The index case was a 61-year-old bedridden woman. Attending village funeral events was associated with COVID-19 infection (Adj.OR=3.57, 95% CI=1.53-8.34), and assisted cooking during the funeral was the highest risk activity. Mask wearing was protective against COVID-19 (Adj.OR=0.12, 95% CI=0.03-0.59). Vaccination was likely to reduce the chance of COVID-19 infection (at least one dose Adj.OR=0.83, 95% CI=0.27-2.57). We ceased the outbreak within one month after the index case was detected. In conclusion, the spreading of the COVID-19 attack among the villagers was contributed by many factors such as social and gathering practice during the funeral events, late detection of cases, and unawareness of COVID-19. Personal preventive measures remain effective against COVID-19. Further study is required to estimate vaccine effectiveness in a specific setting.